Dual presynaptic control by ATP of glutamate release via facilitatory P2X1, P2X2/3, and P2X3 and inhibitory P2Y1, P2Y2, and/or P2Y4 receptors in the rat hippocampus - Rodrigues, Ricardo J. (2005)
ATP is released in a vesicular manner from nerve terminals mainly at higher stimulation frequencies. There is a robust expression of ATP (P2) receptors in the brain, but their role is primarily unknown. We report that ATP analogs biphasically modulate the evoked release of glutamate from purified nerve terminals of the rat hippocampus, the facilitation being mediated by P2X1, P2X2/3, and P2X3 [antagonized by 8-(benzamido)naphthalene-1,3,5-trisulfonate and 2',3'-O-(2,4,6-trinitrophenyl)-ATP] and the inhibition by P2Y1, P2Y2, and/or P2Y4 [antagonized by reactive blue 2 and 2'deoxy-N6-methyladenosine-3',5'-bisphosphate and mimicked by P1-(urinine 5'-),P4-(inosine 5'-) tetraphosphate and 2-methylthio-ADP] receptors. The combination of single-cell PCR analysis of rat hippocampal pyramidal neurons, Western blot analysis of purified presynaptic active zone fraction, and immunocytochemical analysis of hippocampal glutamatergic terminals revealed that the P2 receptors expressed in glutamatergic neurons, located in the active zone and in glutamatergic terminals, were precisely P2X1, P2X2, and P2X3 subunits and P2Y1, P2Y2, and P2Y4 receptors. This provides coincident functional and molecular evidence that P2 receptors are present and act presynaptically as a modulatory system controlling hippocampal glutamate release